Ranger's Apprentice: The Emperor of Nihon-Ja - Book 10 - Flanagan, John (John Anthony) (New York : Philomel Books, 2011)
In a faraway land, a young warrior must protect an emperor from an uprising and train an inexperienced army, with assistance from his Ranger friends.
Originally published: North Sydney, N.S.W. : Random House Australia Children's Books, 2010.
Keywords: Kings and rulers -- Fiction; Fiction